Bulging sign: A precursor of annular rupture observed before aortic balloon rupture during valvuloplasty in transcatheter aortic valve implantation - Hacı Ahmet Kasapkara; Abdullah Nabi Aslan; Tahir Durmaz; Engin Bozkurt (Türk Kardiyoloji Derneği Arşivi, 2016)
Transcatheter aortic-valve implantation (TAVI) is a reliable alternative to surgical aortic-valve replacement in inoperable or high-risk patients. However, this evolving therapy is associated with a wide range of potential complications— some specific to TAVI, some often fatal. Prevention, early recognition, and taking essential precautions will significantly improve results. The case of an 85-year-old woman with balloon rupture during valvuloplasty in TAVI, a very rare and potentially fatal complication, is presented.